Microbially influenced corrosion—Any progress?. (1st July 2020) - Little, B.J.; Blackwood, D.J.; Hinks, J.; Lauro, F.M.; Marsili, E.; Okamoto, A.; Rice, S.A.; Wade, S.A.; Flemming, H.-C.
Highlights: After over 50 years, research has failed to answer fundamental questions related to MIC. Research has not provided tools for detection of MIC in the field. There are no systematic programs to mitigate and prevent MIC. Both require advancement of reliable and predictive MIC models. It is suggested that proactive, integrated approaches be used for MIC prevention and mitigation. Abstract: Microbially influenced corrosion (MIC), is acknowledged to be the direct cause of catastrophic corrosion failures, with associated damage costs ranging to many billions of US annually. In spite of extensive research and numerous publications, fundamental questions relating to MIC remain unanswered. The following review provides an overview of current MIC research and stresses the lack of information related to MIC recognition, prediction and mitigation. The review establishes a link between management decisions and root causes. A holistic, proactive approach to MIC is suggested in which an entire system is considered, monitored and improved.